2022
DOI: 10.1186/s12893-022-01817-3
|View full text |Cite
|
Sign up to set email alerts
|

A 6-year retrospective clinical review of iatrogenic ureteric injuries repaired in a resource-deprived setting

Abstract: Background Seventy percent of ureteric injuries result from iatrogenic causes with about 75% of these diagnosed in the postoperative period. It may have fatal complications such as sepsis and or renal functional damage increasing morbidity and treatment cost. Objective The study aimed to identify the risk factors for iatrogenic ureteric injuries from open surgical procedures and the intervention outcome in a resource-poor setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…They did not find any other predictors regarding previous surgery, previous radiation, diagnosis, type of surgery or demographics. Wei et al 8 found that surgeon inexperience was the main prime risk for these injuries, and Ali et al 6 found that late diagnosis of IUIs were more common amongst non-specialist surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They did not find any other predictors regarding previous surgery, previous radiation, diagnosis, type of surgery or demographics. Wei et al 8 found that surgeon inexperience was the main prime risk for these injuries, and Ali et al 6 found that late diagnosis of IUIs were more common amongst non-specialist surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why younger age and benign indication for hysterectomy predispose for a delayed diagnosis is not clear to us, but one theory that already has been mentioned is surgeon experience 6 , 8 . Our theory is that the more experienced surgeons perform surgery on malignant indication, due to the importance of radical tumour resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, most ureteral injuries are diagnosed postoperatively with variable delays and clinical presentations, making management challenging [ 4 ]. Indeed, management of missed intraoperative ureteral injuries varies widely, from endoscopic treatment allowing cicatrisation of the ureter to more aggressive surgical management ranging from repair of the affected ureter (ureteroneocystostomy, ureteroureterostomy, transureteroureterostomy, ureteral substitution…) to nephrectomy in case of impossible surgical repair or in case of a destroyed kidney [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%